The Cloister life of Charles V. - Stirling Maxwell, William, 1818-1878 (Londen : John C. Nimmo, 1841)
The imperial abdication - The bay of Biscay, Laredo, Burgos, Valladolid - Xarandilla - Servants and visitors - The monastery of St - Jerome of Yuste - State-craft in the cloister - The visit of the Queens - The death of queen Eleanor - The inquisition, its allies and its victims - The death of the emperor - The court of Yuste - Yuste and his Ruins